Tick-Borne Infections. Issue 11 (November 2021) - Fuchs, Susan
Abstract : Abstract: There are many tick-borne infections that affect children and adolescents in the United States. These illnesses often begin with non-specific flulike symptoms such as fever, chills, headache, and myalgia, so obtaining a good travel history is important. Most people do not even realize that they were bitten by a tick, so identification of the specific tick is not necessary. Often, treatment should commence before formal illness identification, as delays may cause more severe disease, and rapid laboratory confirmation is difficult. One of the most important issues is prevention of tick bites with insect repellents, accompanied by thorough tick checks after being outdoors in a tick-infested region.